Analisis Mengenai Dampak Lingkungan Pada Pembangunan Jalan Lingkar Utara Lamongan - Alfina Jana Vian Duri; Devalesio Kumara Wardhana; Mohamad Rahan Ardiansyah; Yohanes Godman Ora Etlatius Woda Sidi; Dika Ayu Safitri (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Every development activity carried out will definitely have an impact on the environment, both positive and negative impacts. The construction of the Lamongan northern ring road is also inseparable from the environmental impacts it causes. Therefore, it is very important to pay attention to how to carry out this development in a way that produces maximum benefits for society while causing minimal negative impacts on the environment. One way to reduce the negative impact of development on the environment is to carry out an Environmental Impact Analysis (AMDAL). AMDAL is a formal and mandatory instrument for every development activity that may have a major impact on the environment. By carrying out an AMDAL, we can analyze the potential environmental impacts that will be caused by a development project and plan ways to reduce these impacts.This research aims to find out the parts of the AMDAL study and AMDAL problems in the Lamongan North Ring Road Construction and provide solutions or ways to overcome these problems. The research results show that activities observed from the aspect of environmental suitability are referred to as environmentally sound. In this case, there is a need for a comprehensive assessment of the potential environmental impacts that may arise as a result of the construction of the Lamongan northern ring road.In carrying out AMDAL, we need to pay attention to various aspects such as the impact on flora and fauna, air and water pollution, land use, and so on. By planning appropriate and sustainable management, we can minimize negative impacts on the environment and maximize the benefits that can be obtained from this development.